DEVELOPMENT OF PROFESSIONAL SELF-DETERMINATION OF TEENAGERS - Milyaeva, Valeriya; Kalyuzhna, Iryna; Burkovska, Zoryana; Lozynska, Svitlana; Voloshanska, Iryna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The article dwells on the problem of teenagers' professional self-determination as the readiness to making choice of the profession. Psychological factors of professional self-determination of high school students are defined and theoretically substantiated. Psychological properties are investigated, the means of which is the formation of factors of senior school students’ professional self-determination. In our research by professional self-determination we mean a stable, value-oriented complex of professionally important traits and personality traits, which is characterized by a certain structure, determines the readiness of high school students to choose a profession and is formed by a number of psychological factors. We prove that the set of psychological factors of professional self-determination of high school students has a nonlinear character and multi-level structure. The purpose of the publication is to investigate the psychological factors of professional self-determination and to substantiate the need to introduce a program of psychological and pedagogical support for the development of professional self-determination of high school students. As a result of the research psychological factors of professional self-determination of high school students were established: actual motives; sufficient level of development of volitional regulation of personality; locus control; a sufficient level of the formation of reflectivity development. The conducted psycho diagnostics revealed the immaturity of psychological factors of professional self-determination among high school students; unreadiness of teenagers to make an independent, conscious professional choice. This situation requires targeted correction through the introduction of a program of psychological and pedagogical support.